Bacteriological Spectrum; Study of Neonatal Conjunctivitis - Rabia Shams, Nusrat Khan, Rubina Kamran (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objectives: To study the bacteriological agents in neonatal conjunctivitis Study Deign: An observational study. Place & duration: The Mother and Child Health Center (MCHC). Pakistan Institute of Medical Science (PIMS) Islarnabad, during the month of N ovember 2008. Material & Methods: All babies born in Mother and Child Health (MCH) nursery PIMS Islamabad in the month of November 2008 were included in the study. Conjunctival swab were taken for gram staining and culture from those with clinical diagnosis of conjunctivitis. Laboratory diagnosis was based on direct smear for gram staining and bacterial culture. Result: A total 1010 babies were delivered. They were examined on first day and enrolled in study, out of which 173 (17.1%) babies developed clinical sign of conjunctivitis. About 50.3% (n=87) babies developed signs of conjunctivitis during first five days of life, while another 22% presented with conjunctivitis on 7th day of life. The total samples sent for Gram staining and culture and sensitivity. Forty-eight (29%) cultures were positive. The most common isolate was Staphylococcus aureus (65% of all positive culture) followed by Klebsiella species (22%). No case of gonococcus organism was isolated. Conclusion: There was a high frequency of neonatal conjunctivitis with Staphylococcus aureus as the most common causative agent. Poor hygienic conditions and practices could be an important risk factor in Pakistan.